Social Support and the Incidence of Cognitive Impairment Among Older Adults in China: Findings From the Chinese Longitudinal Healthy Longevity Survey Study - Yin, Shufei; Yang, Quan; Xiong, Jinli; Li, Tian; Zhu, Xinyi (Frontiers in Psychiatry, 2020)
Objective Social support shows a protective effect against cognitive impairment in older adults. However, the longitudinal relationship between the distinct sources of social support and the incidence of cognitive impairment remains unclear. This study aims to investigate the association between different sources of social support and the incidence of cognitive impairment among older adults in China. Method We used longitudinal data (2005–2014) from the Chinese Longitudinal Healthy Longevity Survey (CLHLS, 2005–2014, mean follow-up years 5.32 ± 2.64). In total, 5897 participants (aged 81.7 ± 9.7 years, range 65–112 years, 49.0% male) were enrolled. Cognitive impairment was measured by the Mini-Mental State Examination (MMSE). Social support included support from family and friends (marital status; contacts with family and friends; children's visits; siblings' visits, sick care; money received from and money given to children) and the availability of support from social community (social service and social security). We calculated subdistribution hazard ratios (SHR) of cognitive impairment by establishing Cox regression models, adjusting for residence, gender, age, education, participation in physical exercise, activities of daily living, smoking, drinking, negative psychological well-being, baseline cognitive function, occupation, leisure activities, and diseases. Results During a 9-year follow-up, 1047 participants developed cognitive impairment. Participants who were married had a 16.0% lower risk of developing cognitive impairment compared to the widowed older adults after controlling for all covariates, but the protective effect of being married was no longer significant (p = 0.067) when additional adjustment was made for all types of social support. Children's visits were significantly associated with the risk of cognitive impairment after controlling for all types of social support and covariate variables (SHR = 0.808, 95% confidence interval, 0.669–0.975, p = 0.026). Conclusion Children's visits were consistently associated with a lower incidence of cognitive impairment in Chinese older adults.